The mission house : a novel - Davies, Carys (Scribner, 2021)
Taking refuge in a mission house in a remote hill town in India, an Englishman fleeing the dark undercurrents of contemporary life bonds with a Padre's daughter against a backdrop of escalating religious tensions.